Methods of comparative analysis in the study of samples of Uzbek and world literature - Abduvalitov Nurzhan Buranovich; Abduvalitov Ergash Buranevich (The Bioscan, 2024)
This article examined the question of scientific and theoretical justification of the method of comparative analysis of the study of Uzbek literature in combination with world literature. The issues of studying world and Uzbek literature in harmony are also widely covered, on the one hand, students' mastering in organic relations the most striking examples of world literature, on the other hand, the insufficient methodological development of the problem of comparative study of Uzbek and foreign literature